(untitled) (Global Journal of Human-Social Science, 2021)
This paper is intended to explore Fauziya Kassindja’s autobiography, Do They Hear You When you Cry (1998), Kassindja’s psyche, who was subjected to a sequence of traumas in her adolescent life, death of her father, escaping Female genital Mutilation, and imprisoned for being illegal immigrant as she was an asylum seeker. This work attests the positive effects of the trauma in changing her life forever, changing from innocent to experience. It concentrates on revealing the result of human growth after trauma upon Stephen Joseph and P. Alex Linley theoretical perception of posttraumatic stress and the organismic valuing theory as exposed in Trauma,Recovery and Growth: Positive Psychological Perspectives on Posttraumatic Stress (2008). Kassindja writes her autobiography as part of cognitivebehavioral therapy after adversity, as she discloses her detailed emotions of every experience she went through from her traumatic memory. I conclude that Kaassindja used writing her autobiography as a kind of self-therapy that her consciousness exercised to overcome her experience. Therefore, she lives her life to the better not to the worst.